Facing “Goliath” in public speaking: communication apprehension among Malaysian tertiary learners / Joseph Alagiaraj Thambu Raj, Asmaa AlSaqqaf and Lindey Easter Apolonius - Thambu Raj, Joseph Alagiaraj; AlSaqqaf, Asmaa; Apolonius, Lindey Easter (Universiti Teknologi MARA, 2024)
Communication apprehension, which refers to the fear or anxiety experienced in classrooms, is a considerable obstacle for Malaysian tertiary learners, especially in public speaking scenarios. This paper presents a general overview of published studies of communication apprehension in public speaking among Malaysian learners since 2019. This systematic literature review examines two research questions: what are the causes of communication apprehension among Malaysian tertiary learners and what are the most effective strategies to overcome communication apprehension in public speaking. Fifteen studies were thoroughly reviewed. The results indicate that the majority of tertiary learners in Malaysia generally have a moderate level of communication apprehension, which is mostly caused by the fear of being evaluated, anxiousness, and a lack of self-efficacy abilities. It also showed female learners were more courageous to face apprehension in public speaking than males. Several strategies suggested to address communication apprehension are by modifying teaching methods, creating positive and stress-free classroom environments and giving positive and constructive feedback